Arabic Manuscripts in the Birnbaum Collection, Toronto : A Brief Catalogue - Birnbaum, Eleazar, (Islamic Manuscripts and Books, 2019)
Arabic and Persian Manuscripts in the Birnbaum Collection, Toronto includes many early copies, from the 6th century A.H. / 12th century C.E. onwards. They cover a wide range of subjects. The catalogue gives detailed descriptions of 66 Arabic and 34 Persian works, arranged by subject. Author and title indexes provide easy access, and photographs of selected pages enhance the descriptions. The manuscripts were acquired individually over many decades.